2023
DOI: 10.1136/jech-2022-220247
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of social prescribing for chronic disease prevention in adults: a systematic review and meta-analysis of randomised controlled trials

Abstract: BackgroundSocial prescribing (SP) enables healthcare professionals to link patients with non-medical interventions available in the community to address underlying socioeconomic and behavioural determinants. We synthesised the evidence to understand the effectiveness of SP for chronic disease prevention.MethodsA systematic literature search was conducted using five databases and two registries. Eligible studies included randomised controlled trials of SP among community-dwelling adults recruited from primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…By illuminating the potential influence of specific social activities on dementia risk among older individuals, our findings could inform the development of population health strategies aimed at preventing or delaying the onset of dementia. This, in turn, may support the progress of social prescribing initiatives—a concept in which health care professionals link individuals with nonmedical sources of support, such as community-based social activities and resources ( Htun et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…By illuminating the potential influence of specific social activities on dementia risk among older individuals, our findings could inform the development of population health strategies aimed at preventing or delaying the onset of dementia. This, in turn, may support the progress of social prescribing initiatives—a concept in which health care professionals link individuals with nonmedical sources of support, such as community-based social activities and resources ( Htun et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence found could be used by policy makers and health care professionals to set appropriate guidelines and policies and to improve patient outcomes through nonmedical interventions, such as social prescribing. 152 Because SDoH are currently overlooked in predicting health outcomes, including CVD, 153 , 154 , 155 , 156 and because our review identified that SDoH factors have a role in CVD and CVD mortality, we recommend that future clinical CVD prediction models should include the SDoH.…”
Section: Discussionmentioning
confidence: 99%
“…‘Social prescribing’ can be defined as a process that enables healthcare professionals to refer patients to a link worker to initiate a non-clinical social prescription to improve their health and well-being [ 66 , 67 ]. Social prescribing is being proposed as a solution to poor social health, as an innovative holistic community-centred approach [ 68 ]. There are systematic reviews demonstrating benefits of social prescribing to well-being [ 69 , 70 ] and quality of life [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are systematic reviews demonstrating benefits of social prescribing to well-being [ 69 , 70 ] and quality of life [ 71 ]. A recent systematic review identified that while there was a lack of evidence on social prescribing for chronic disease risk factors, the few group-exercise programs that were identified had benefits for physical activity [ 68 ]. The authors highlight that social prescribing could be effective in improving social health, as well as modifying the determinants of chronic diseases and promoting sustainable healthy behaviours.…”
Section: Discussionmentioning
confidence: 99%